The prevalence of expression of MAGE-A3 and PRAME tumor antigens in East and South East Asian non-small cell lung cancer patients. (November 2016) - Thongprasert, Sumitra; Yang, Pan-Chyr; Lee, Jung Shin; Soo, Ross; Gruselle, Olivier; Myo, Aung; Louahed, Jamila; Lehmann, Frédéric F.; Brichard, Vincent G.; Coche, Thierry
Highlights: MAGE-A3 and PRAME tumor antigen co-expressed in 20% of NSCLC tumors of Asian patients. Higher rates of antigen-positive tumors in squamous cell carcinomas. Higher rates of antigen-positive tumors in samples from smoking patients. Expression of MAGE-A3 and PRAME associated with tumor histology and smoking status. MAGE-A3 and PRAME as potential targets for antigen-specific immunotherapy. Abstract: Introduction: Treatment of non-small cell lung cancer (NSCLC) is an important and often unmet medical need regardless of the disease stage at the time of first diagnosis. Antigen-specific immunotherapy may be a feasible therapeutic option if tumor associated antigens (TAAs) that can be targeted by the patient's immune system are identified. The study objective (NCT01837511) was to investigate the expression rates of MAGE-A3 and PRAME in tumors from East Asian NSCLC patients, and the associations between TAA expression and clinico-pathologic patient characteristics. Methods: Archived formalin-fixed paraffin-embedded tumor tissue specimens were tested for MAGE-A3 and PRAME expression by quantitative reverse transcription polymerase chain reaction. Exploratory analyses of the impact of patient and tumor characteristics on antigen expression were performed by multivariate logistic regression analyses. Results: A total of 377 specimens were tested and a valid expression result was obtained for 86.5% and 92.6% for MAGE-A3 and PRAME, respectively. Of the specimens with valid test results, 26.4% expressed MAGE-A3, 49.9% PRAME, 20.0% both and 57.5% expressed at least one TAA. The same pattern of associations between antigen expression and patient and tumor characteristics was found for both TAAs: higher rates of antigen-positive tumors were found in squamous cell carcinomas compared to adenocarcinomas, and for smokers compared to non-smokers. Conclusions: Expression of MAGE-A3 and PRAME suggests an association with tumor histology and the patient's smoking status. The rates of TAA-positive tumors found in these East and South East Asian NSCLC patients indicate that both antigens may serve as targets for antigen-specific immunotherapies.